The influence of financial distress, independent commissioner, audit tenure, and institutional ownership on financial statement integrity - Anita Ardiyanti; Dirvi Surya Abbas; Suparman (LPPM UBP, 2026)
This study aims to analyze the effect of financial distress, independent commissioners, audit tenure, and institutional ownership on the integrity of financial statements in non-cyclical customer sector companies in Indonesia listed on the Indonesia Stock Exchange from 2021 to 2024. Data were obtained from financial statements using multiple regression analysis. The sample used in this study consisted of 131 companies selected using purposive sampling, taking into account several predetermined criteria. The data were analyzed using panel data regression techniques with the help of E-views 12 software. The results of this study indicate that FD and AT have a significant effect on financial statement integrity, while independent commissioners and institutional ownership have no effect on financial statement integrity.